Knowledge and transmission risk awareness of tuberculosis among the pilgrims attending a religious mass gathering in India: a cross-sectional study - Tim Bäckdahl; Megha Sharma (BMC, 2021)
Abstract Background Tuberculosis infection accounts for more annual deaths than any other single infectious disease, except the Corona Virus infection. It is a significant global issue and India is one of the most affected countries. Religious mass gatherings congregate millions of pilgrims at one place. Over-crowding is a high-risk factor for the transmission of tuberculosis. Knowledge and awareness of the disease are proven prerequisites for the spread-prevention and early diagnosis of tuberculosis. The present study was designed to explore the knowledge of tuberculosis and awareness of disease transmission risk among pilgrims attending a religious mass gathering, the Kumbh Mela (2016) in Ujjain, India. Methods Self-reported data on the pilgrims' tuberculosis-knowledge were collected using a cross-sectional study design. A contextual, pre-tested questionnaire was used, using the convenience sampling method. In addition to the anonymous descriptive analyses, a composite knowledge-score was developed to enable comparisons between demographic groups. Results In total, 1665 pilgrims participated in the study with 38.8 years of mean age and 59% literacy rate. The most recognized symptoms of tuberculosis were "Cough for more than 15 days with sputum" (94%) and "Blood in sputum" (81%). Most participants knew that tuberculosis is an infectious disease (93%) and not hereditary (91%). Additionally, 84% considered it is a potentially lethal disease that requires extensive treatment. However, vaccine awareness was poor (4%). "Direct contact with tuberculosis patient" (78%) and "To be in a crowded area" (4%) were considered as the most important risk factors for tuberculosis transmission. For the composite knowledge-score, a significantly higher mean score was seen among those with at least ten years of schooling compared with illiterates (p <  0.001). Occupation and residency also affected the mean score. Conclusion Most pilgrims attending the Kumbh Mela had basic knowledge of the characteristics of tuberculosis, but some important knowledge gaps concerning the transmission risks associated with crowded situations existed. These gaps need to be addressed in future policies to enable safer mass gatherings and to end the TB epidemic, globally.